Norms that matter: Exploring the distribution of women's work between income generation, expenditure-saving, and unpaid domestic responsibilities in India - Ashwini Deshpande; Naila Kabeer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Based on primary data from India, this paper analyses the reasons underlying women's low labour force participation. In developing countries, women engaged in unpaid economic work in family enterprises are often not counted as workers. Women are involved in expenditure-saving activities, i.e. productive work within the family, over and above domestic chores and care work. We document the fuzziness of the boundary between domestic and unpaid (and therefore invisible) productive work which leads to mismeasurement of women's work. Religion and visible markers such as veiling are not significant determinants of the probability of being in paid work, but the social norm that matters as a major constraint is that of being primarily responsible for domestic chores. We demonstrate the existence of 'virtuous cycles' within families: a history of working women in the family increases the probability of being in paid work by between 18 and 21 percentage points.
Keywords: J16; J21; J40; B54; 330; women; labour force participation; India; social norm; unpaid economic work